A new genus and species of Caribbean forest lizard (Diploglossidae; Celestinae) from southern Hispaniola - Landestoy T., Miguel A.; Schools, Molly; Hedges, S. Blair (Zootaxa, 2022)
A new genus and species of Caribbean forest lizard of the subfamily Celestinae Schools & Hedges are described. This new taxon is known only from two small adjacent keys in the Laguna de Oviedo of the Parque Nacional Jaragua in the Barahona Peninsula, Dominican Republic, at the southernmost region of the Caribbean island of Hispaniola. The genus Guarocuyus gen. nov. is genetically more closely related to the clade containing Celestus Gray, Comptus Schools & Hedges, and Panolopus Cope; nevertheless, we compare it to all celestine genera. Morphologically, it differs from other celestines by having an interdigital web on three toes and by having the widest ear opening. Additionally, the species Guarocuyus jaraguanus sp. nov. has some ecological attributes that when combined, appear to be unique, including nocturnal habits, a semiprehensile tail, and a facultatively arboreal lifestyle. We note sexual dimorphism in the new species and in two other celestines, Caribicus darlingtoni (Cochran) and the poorly known Celestus macrotus Thomas & Hedges, and report a range extension of the latter species into the Dominican Republic. We also discuss several scale topography conditions considered of taxonomic value for the group.